2016
DOI: 10.1016/j.cemconres.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high mixing intensity on rheology, hydration, and microstructure of fresh state cement paste

Abstract: From both the fundamental and applied points of view, there is a growing interest in characterizing the rheological properties of concentrated suspensions, such as cement paste. When a cement paste is sheared, its intrinsic network structure will respond to the shear induced stresses. The influence of mixing intensity on the rheological properties of fresh state cement paste is studied. The results showed that contrary to what is popularly believed, when subjected to a high mixing intensity the rheological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(31 citation statements)
references
References 45 publications
(52 reference statements)
2
27
0
2
Order By: Relevance
“…It is widely known that the loss of fluidity of cement pastes may be affected by a number of factors, such as cement hydration, mixing procedure, as well as type, dosage and addition mode of superplasticizers, specifically, those based on Polycarboxylate Ether polymers (PCEs) [1][2][3][4][5][6][7]. The fact that these parameters can act simultaneously makes very challenging to describe flow loss in quantitative terms.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known that the loss of fluidity of cement pastes may be affected by a number of factors, such as cement hydration, mixing procedure, as well as type, dosage and addition mode of superplasticizers, specifically, those based on Polycarboxylate Ether polymers (PCEs) [1][2][3][4][5][6][7]. The fact that these parameters can act simultaneously makes very challenging to describe flow loss in quantitative terms.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the PSD could have been expected due to shearing during paste preparation. In fact, using focused beam reflectance measurements, Han and Ferron (2016) observed that the size of weakly linked agglomerates increases at a high mixing speed. However, it should be pointed out that high dilution rates as well as agitation during measurement might hide differences in the dispersion states of the dilution liquids (Williams et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to consistency, it could be stated that cement-lime mortars were more sensitive to changes in the mixing procedure than mortars with APA (Tables 19 and 20). This effect might be due to the possibility of uneven distribution of lime in cement-lime mortars, which could occur at high or very low mixing speeds [79]. The admixture was added to the water and mixed by hand, and then added together with water to the mortar, and, therefore, the mixing speed might not be as crucial to an even distribution of the APA in the mortar.…”
Section: Impact Of Mixing Intensitymentioning
confidence: 99%